The world and the kingdom: historicity and fictionalization in Alejo Carpentier's novel the kingdom of this world - Vargas, Fábio Aristimunho (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2018)
The novel El mundo de este mundo(1949), by Cuban writer Alejo Carpentier (1904-1980), is a work of historical fiction that portrays the French colony of Saint-Domingue in the XVIII century until the first decades of independent Haiti, introducing the style of narrative known as "marvelous real", which would greatly influence the XX century’s Latin American literature. Although the narrative does not mention dates or facts, it is possible to recognize and date the main events portrayed, as well as to identify certain real characters that appear in the plot. The present article seeks to uncover the historical elements referred to and fictionalized by Carpentier throughout his work, seeking to separate the (real) world of the realm (of fiction), in order to provide subsidies for a better understanding of the narrative. For this, this article analyzes the four parts of the book, contrasting the narrativewith historical facts and elements of the theory of historical fiction.